An assessment of the contribution of customer relationship management on bank performance the case of people’s Bank of Zanzibar limited - Abdalla, Zainab.S (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for award of the Degree of Master of Business Administration (MBA) of Mzumbe University